2017
DOI: 10.1111/ijsw.12294
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and gendered identity constructions in labour activation

Abstract: Few studies have considered how labour activation programmes affect participants’ identity construction, particularly from a gender comparison perspective. Using qualitative data and recognition theories, this exploratory study of the Norwegian Qualification Program examined how gender may affect labour activation recipients’ identity construction and sense of social value. The findings suggest that women experience labour activation as an enabling process, facilitating an enhanced sense of social value and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Such institutional barriers may in turn lead to prolonged activation trajectories: participants continue to lack relevant and necessary qualifications and may suffer from a lock-in effect precipitated by insufficient and inadequate measures and support (Fossestøl et al, 2016b). Concurrently, they may produce demotivated, disillusioned participants (Hansen, 2018) with large gaps in their CVs, which in turn may result in participants being further removed from the labour market.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such institutional barriers may in turn lead to prolonged activation trajectories: participants continue to lack relevant and necessary qualifications and may suffer from a lock-in effect precipitated by insufficient and inadequate measures and support (Fossestøl et al, 2016b). Concurrently, they may produce demotivated, disillusioned participants (Hansen, 2018) with large gaps in their CVs, which in turn may result in participants being further removed from the labour market.…”
Section: Resultsmentioning
confidence: 99%
“…However, research on service users' experiences has indicated that activation policy implementation does not necessarily respond to service users' actual needs. Even though service users may have positive experiences when encountering social workers (Skjefstad, 2013;Hansen and Natland, 2017), their expectations related to acquiring work as a result of participating in an activation programme are rarely fulfilled (Gubrium, 2014;Hansen, 2018). Failure to obtain paid employment may in turn lead to disillusioned service users who experience a loss of social value and status regarding their employability and labour market attachment (Gubrium, 2014;Hansen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, activising these users and providing them with labour market programmes has been increasingly emphasised since the early 1990s (Djupvik & Eikås, 2016). The goal has been to prevent poverty and social exclusion and enable these young people to support themselves through paid work (Hansen, 2018;Lødemel & Moreira, 2014). In parallel, the users have been charged with more personal responsibility and the requirement for activation and participation has escalated (Wright, 2012;Lundberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We learned about gendered poverty experiences from previous studies that poor men plan their future for only a short period or lack a future orientation entirely. Men also experience more profound feelings of worthlessness than women do (Hansen, 2018;Isola, Siukola, & Kukkonen, 2019). Third, we have made the abstractions of the findings, being aware that they may not include some aspects of the broad spectrum of experiences and that there are some exceptions that the material also includes that we have not covered in this study.…”
Section: The Longitudinal Narrative Research Setting Materials Information: Features Choices and Limitationsmentioning
confidence: 99%